Customer management in financial services - Machtynger, Liz (Henry Stewart Talks, 2008)
The changing environment for customers, Market pressures and opportunities, Customer management definition, Drivers of customer management, Delivering successful customer management, Customer management in financial services: progress and challenges, Benchmarks, The future of customer management for financial services